Evaluation of the Development of Women's Employment Laws in an Islamic State: The Case of Islamic Republic of Iran (1989-2017) - Jahanipour Sagez Abadi, Zeinab (Journal of History Culture and Art Research, 2020)
The researcher in this paper attempts to examine and analyze the factors of underdevelopment in women's employment in the Islamic Republic of Iran. The goal of this paper was to assess the implementation of women's employment development laws in the Islamic Republic of Iran from 1989 to 2017. This research paper examined the text of laws, policies, and interviews with key informants through the theories of occupational inequality, gender theories, and feminism. The results show that despite policies and planning for the development of women's employment, the necessary infrastructure to enhance women's employment is still lacking. Whereas the identity and personality of individuals in Iranian society are formed among the family; the role of the family is therefore significant, that adds to its importance in preserving and affecting it. In other words, Iranian society is confronted with a two-tiered structure of social policy and family-oriented discourse, and different governments apply different development policies with respect to their certain method to the family institution. During periods of supportive policies that lead to women being excluded from employment, and in other periods, focusing on the issue of gender rights and freedom, policies are being developed that encourage women to participate more economically. However, what stands out among them is the centrality and power of the family in society that raises such issues and challenges in the development of women's employment.